2020
DOI: 10.3390/cancers12061477
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Role of Estrogen Receptor β in Triple-Negative Breast Cancer

Abstract: Estrogen receptors (ERα and ERβ) are ligand-activated transcription factors that play different roles in gene regulation and show both overlapping and specific tissue distribution patterns. ERβ, contrary to the oncogenic ERα, has been shown to act as an oncosuppressor in several instances. However, while the tumor-promoting actions of ERα are well-known, the exact role of ERβ in carcinogenesis and tumor progression is not yet fully understood. Indeed, to date, highly variable and even opposite effects have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 191 publications
(285 reference statements)
0
38
0
1
Order By: Relevance
“…As a known tumor suppressor, persistent ERβ expression is associated with a less aggressive and non-invasive phenotype, and prolonged patient survival [ 249 ]. ERβ expression is retained in 30% of TNBCs, whereas its expression is lost in 70% of TNBC [ 250 , 251 ]. For ERβ-positive TNBC cells, adding estrogen (E2) or other ERβ-selective agonists to activate ERβ receptor can elicit potent anticancer effects by inducing cystatin gene expression, decreasing cell proliferation, inhibiting canonical TGFβ pathway activation, blocking epithelial-to-mesenchymal transition, and preventing malignant cell invasion and metastatic spread [ 252 , 253 , 254 , 255 , 256 , 257 ].…”
Section: Emerging Targeted Therapies In Tnbcmentioning
confidence: 99%
“…As a known tumor suppressor, persistent ERβ expression is associated with a less aggressive and non-invasive phenotype, and prolonged patient survival [ 249 ]. ERβ expression is retained in 30% of TNBCs, whereas its expression is lost in 70% of TNBC [ 250 , 251 ]. For ERβ-positive TNBC cells, adding estrogen (E2) or other ERβ-selective agonists to activate ERβ receptor can elicit potent anticancer effects by inducing cystatin gene expression, decreasing cell proliferation, inhibiting canonical TGFβ pathway activation, blocking epithelial-to-mesenchymal transition, and preventing malignant cell invasion and metastatic spread [ 252 , 253 , 254 , 255 , 256 , 257 ].…”
Section: Emerging Targeted Therapies In Tnbcmentioning
confidence: 99%
“…Although TNBC is defined as negative for both ER-α and PgR, some TNBC express other sex steroid hormone receptors: AR [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], ER-β [ 27 , 28 , 29 , 30 , 31 , 32 ], or GPER [ 33 , 34 , 35 , 36 , 37 , 38 ]. AR and ER-β belong to the ER type subgroup of the nuclear receptor superfamily, and typically transmit genomic signaling; however, the existence of non-genomic signaling pathways through these receptors or non-nuclear receptors located in the cytoplasmic membrane or cytoplasm has been reported and attracted attention.…”
Section: Sex Steroid Hormone Receptors Other Than Er-α and Pgrmentioning
confidence: 99%
“…Hormone (estrogen) unresponsiveness is considered the fundamental characteristic of TNBC; however, studies have revealed the expression of some sex steroid hormone receptors other than classic ER (now renamed ER-α) in TNBC; that is, androgen receptor (AR) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], second ER (namely ER-β) [ 27 , 28 , 29 , 30 , 31 , 32 ], or non-nuclear receptors represented by G-protein-coupled estrogen receptor (GPER) [ 33 , 34 , 35 , 36 , 37 , 38 ]; suggesting the biological and/or clinical relevance of sex steroid hormones in TNBC. Physiologically present androgens and estrogens are made of cholesterol, and commonly have a steroidal structure [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCF-7 cell line has been shown to express both ERα and ERβ (26). Although ERβ has been suggested as a cancer therapeutic target (27), some studies (28) show that when ERα/β positive MCF-7 cells are treated with an active metabolite of BPA [4-methyl-2,4-bis(4-hydroxyphenyl)pent-1-ene (MBP)] at levels (∼1 nM) comparable to human environmental exposure, ERα protein expression is downregulated and proliferation is increased via ERβ. In particular, the MCF-7 proliferation stimulated by MBP is dose-dependently counteracted by the cotreatment with the selective ERβ antagonist PHTPP (4-[2phenyl-5,7-bis (trifluoromethyl) pyrazolo [1,5-a]-pyrimidin-3yl] phenol).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%